Understanding generational differences impact on employee relationships with co-workers, on individual performance and engagement in the workplace - Maja, Makgotso Birtha (My University, 2017)
The multifaceted workplace, encompassing different generations, has been seen to have its benefits and potential factors leading to conflict (Burke, 2004). Differences existing within generations often influence the organizational success, staff performance, satisfaction, creativity, group cohesion and reputation, resulting in satisfactory or unsatisfactory relations being established (Baptiste, 2009; Saba, 2013; Salahuddin, 2010). Intergenerational differences provide additional insight into work life forces impinging on human beings within the workplace, which ultimately influences the success of the organization (Gratton, 2011; Salahuddin, 2010). As such, this study will provide additional insight into how generational differences impact on employee relationships with co-workers, on individual performance, and engagement in the workplace. The qualitative research approach was used to elicit live experiences of participants, and the narrative study design applied to, efficiently allowed participants to share their story. Using interview schedules, interviews were conducted with sixteen participants selected through a nonprobability purposive sampling strategy. Semi-structured interviews were conducted following obtainment of consent from the participants, and interviews were recorded and transcribed verbatim. Data was analysed using thematic analysis whereby data was divided into themes and subthemes, interweaving these within existing literature. The study anticipated that the changing workforce influences diverse generations differently, and this has an influence on the relations established and the manner in which they respond to the changes, and in so doing meets the organizational needs. The study found that similarities exist amongst generational groups which include: access to opportunities, performance and workforce needs. The findings also show that workplace challenges exist, however, and through the use of survival strategies employees can cope when presented with challenges. The study has provided insight on how occupational social workers can develop organizational strategies and interventions, which seek to acknowledge and embrace diversity amongst employees, in order to successfully manage and work effectively with a multigenerational workforce.
A Report on Research Study presented to the Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand in partial fulfilment of the requirements for the degree Master of Arts in Occupational Social Work, March 2017
Keywords: Baby boom generation--Employment--South Africa; Generation X--Employment--South Africa; Generation Y--Employment--South Africa; Employee motivation--South Africa; Job satisfaction--South Africa